Experimental study on the fire resistance of GFRP pultruded tubular beams. (15th April 2018) - Morgado, T.; Correia, J.R.; Silvestre, N.; Branco, F.A.
Abstract: This paper presents an experimental study about the fire resistance behaviour of pultruded glass fibre reinforced polymer (GFRP) beams. The main objectives of the study were to evaluate the influence on the fire resistance of GFRP beams of (i) the number of sides exposed to fire; (ii) the load level applied, and (iii) using different fire protection systems. To this end, a total of 12 GFRP tubular beams were exposed to the time-temperature curve of ISO 834, in either one or three sides, and simultaneously subjected to two different load levels corresponding to mid-span deflections of L/400 or L/250, L being the span. Different passive and active fire protection systems were assessed, including thick insulation boards, intumescent products and water-cooling. The results obtained show that three-side exposure causes a remarkable reduction of fire resistance, compared to one-side exposure, for both unprotected and protected profiles, highlighting the importance of adopting a building architecture with GFRP beams integrated in the floors. The efficacy of water-cooling for one-side exposure was confirmed; however, for three-side exposure it is shown that only passive protection is able to significantly extend the fire endurance of GFRP pultruded profiles. As expected, increasing the load level caused a (moderate) reduction of fire resistance.